The United States occupation of Haiti, 1915-1934 - Schmidt, Hans, 1938- (Rutgers University Press, 1995)
"Detailed and useful history of US intervention in Haiti (1915-34); originally published in 1971, and re-released in 1995 at the time of the US invasion of Haiti. Contains many interesting insights"--Handbook of Latin American Studies, v. 57.